Catalytic enantioselective aza-piancatelli rearrangement - Gade, Amol B.; Patil, Nitin T. (Synlett, 2017)
The design and development of an enantioselective aza-Piancatelli rearrangement reaction are described. In the presence of a chiral phosphoric acid catalyst, furylcarbinols react with anilines to afford highly functionalized cyclopentenones with excellent diastereo-and enantioselectivities. The process was shown to be scalable, and up to 1 gram of starting material could be employed under mild reaction conditions.